Healthy lifestyle and normal waist circumference are associated with a lower 5-year risk of type 2 diabetes in middle-aged and elderly individuals: Results from the healthy aging longitudinal study in Taiwan (HALST). Issue 6 (February 2017) - Chen, Chu-Chih; Liu, Kiang; Hsu, Chih-Chen; Chang, Hsing-Yi; Chung, Hsiao-Chun; Liu, Jih-Shin; Liu, Yo-Hann; Tsai, Tsung-Lung; Liaw, Wen-Jin; Lin, I-Ching; Wu, Hsi-Wen; Juan, Chung-Chou; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Type 2 diabetes mellitus (DM) is known to be closely associated with lifestyle and obesity and has a prevalence that increases with age. This study aimed to assess the short-term composite effect of diet, physical activity, psychosocial health, and waist circumference (WC) on the incidence of DM in the elderly and to provide a lifestyle-based predictive index. We used baseline measurements (2009–2013) of 5349 community-dwelling participants (aged 55 years and older, 52% female) of the Healthy Aging Longitudinal Study in Taiwan (HALST) for fasting plasma glucose, HbA1C, serum cholesterol, triglycerides, blood pressures, WC, and outcomes of home-visit questionnaire. Principal component analysis (PCA) was used to identify participants with a healthy lifestyle (HLF: higher diet, physical activity, and psychosocial scores) and a lower WC, with cutoffs determined by the receiver-operating characteristics. A Cox regression model was applied to 3424 participants without DM at baseline by linking to their National Health Insurance records (median follow-up of 3.1 years). In total, 247 new DM cases (7.2%) were identified. The HLF and lower WC group had a relative risk (RR) of DM of 0.54 (95% CI 0.35–0.82) compared to the non-HLF and higher WC group. When stratified by the presence of impaired glucose tolerance (IGT) or metabolic syndrome (MS), only participants with IGT/MS showed significant risks (RR 0.55; 95% CI 0.33–0.92). However, except for WC, the individual lifestyle factors were nonsignificant in the overall model without PCA. A composite protective effect of HLF and normal WC on DM within 5 years was observed, especially in those with IGT or MS. Psychosocial health constituted an important lifestyle factor in the elderly. The cutoffs identified could be used as a lifestyle-based risk index for DM. Maintaining an HLF to prevent DM is especially important for the elderly.